If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 4 = 3a Reorder the terms: 4 + 3x = 3a Solving 4 + 3x = 3a Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 3x = -4 + 3a Combine like terms: 4 + -4 = 0 0 + 3x = -4 + 3a 3x = -4 + 3a Divide each side by '3'. x = -1.333333333 + a Simplifying x = -1.333333333 + a
| 6/10z=-2 | | 7/8x18 | | K^2+9=39 | | 2m-4+11m=7m-19+3m | | x(x+9)-3=9x+1 | | 7=2c-4 | | 1.4x-3.1=.2(x-27.5) | | 4x=15x+4 | | x=5.666666667+2.333333333y | | -4x+7=-2+4x | | 17x+13y=-17 | | x+2(0)=-8 | | 21x-3=17y-9 | | 90=4x-2 | | 15.5/2.5 | | (-6+4i)+(7-2i)=0 | | a/5-4=12 | | Sin(4x)-cos(2x)=0 | | 100(4/5) | | 5x+-7(-1x+2)=58 | | -2d-7+3d=16 | | u=7(x-2) | | 0=-2x^2+6x-n | | 9x^3-24x^2+12x+7=0 | | 5x-7y(-x+2)=58 | | 90+x+x^9=180 | | (u+8)(u-3)= | | x^2-2x-7=2x+14 | | u=4x-18 | | 9x^2+14+5=0 | | X^2+7x+9= | | 15y+10x-3=6 |